1989
DOI: 10.1113/expphysiol.1989.sp003352
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Acute Cardiovascular Responses to Haemorrhage by Tissue Injury in the Conscious Rat

Abstract: SUMMARYA moderate haemorrhage of 0-75 + 0-09 ml (100 g body weight)-1 (I 111 + 1-3 % of estimated blood volume) in the conscious rat produces a tachycardia, possibly mediated by the baroreflex, which serves to maintain mean arterial blood pressure. A severe haemorrhage of 120 + 006 ml (100 g)-1 (> 195 + 1[5 % of estimated blood volume) produces a bradycardia and mnarked hypotension. The bradycardia is reflex in nature and is due to an increased vagal efferent activity to the heart. This bradycardia is markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
41
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 16 publications
(29 reference statements)
6
41
0
Order By: Relevance
“…In humans, parasympathetic activation has been shown to be involved in the bradycardia associated with lower body negative pressure-induced hypovolemia (32). Previous studies in the literature suggest that reflex vagal activation is involved in the bradycardia associated with hypovolemia in the rat model of hemorrhagic shock (18,21). Parasympathetic activation is a possible mechanism for the overshoot observed in Raw on blood volume restoration.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, parasympathetic activation has been shown to be involved in the bradycardia associated with lower body negative pressure-induced hypovolemia (32). Previous studies in the literature suggest that reflex vagal activation is involved in the bradycardia associated with hypovolemia in the rat model of hemorrhagic shock (18,21). Parasympathetic activation is a possible mechanism for the overshoot observed in Raw on blood volume restoration.…”
Section: Discussionmentioning
confidence: 99%
“…inhibition) and maintenance of blood pressure via the arterial baroreceptor reflex (Secher & Bie, 1985;Little et al 1989). As haemorrhage progresses, and blood loss exceeds 20-30 % of total blood volume, a depressor phase becomes apparent.…”
mentioning
confidence: 99%
“…As haemorrhage progresses, and blood loss exceeds 20-30 % of total blood volume, a depressor phase becomes apparent. This involves a vagally mediated bradycardia (inhibited by atropine, Little et al 1989), a reduction in peripheral vascular resistance (Barcroft et al 1944;Evans & Ludbrook, 1991) and a marked fall in arterial blood pressure. This second phase is not due to a failure of the baroreflex, since the latter's sensitivity is increased at this stage (Little et al 1984), nor is it a preterminal event (Hoffman, 1972;Sander-Jensen et al 1986), but rather it is due to the activation of additional reflex(es).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it appears that the element of neural activity involved in producing the 'injury'-like effects of sciatic stimulation are mediated via small diameter fibres (possibly C fibres); recent studies have shown that stimulation of the sciatic nerve attenuates the vagal bradycardia seen when cardiac afferent fibres are activated. This mimics the effects of real injury on the bradycardia associated with a severe haemorrhage (Little, Marshall & Kirkman, 1989), and is dependent on small, rather than large, somatic afferent fibre activity in the sciatic nerve since it cannot be abolished by cooling the sciatic nerve to 3°C, which blocks transmission in large myelinated fibres (E. Kirkman, J. R. Banks, H. W. Marshall & R. A. Little, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%